2012
DOI: 10.1063/1.4759137
|View full text |Cite
|
Sign up to set email alerts
|

Sb concentration dependent structural and resistive properties of polycrystalline Bi-Sb alloys

Abstract: Polycrystalline Bi 1-x Sb x alloys have been synthesized over a wide range of antimony concentration (0.08 < x < 0.20) by solid state reaction method. In depth structural analysis using X-Ray diffraction (XRD) and temperature dependent resistivity () measurement of synthesized samples have been performed. XRD data confirmed single phase nature of polycrystalline samples and revealed that complete solid solution is formed between bismuth and antimony.Rietveld refinement technique, utilizing MAUD software, has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…32 The Bi rich semiconducting Bi 1Àx Sb x alloys discussed here possess similar band picture. 27,30 Hence, in accordance with Baraff, it is justified to assume that observed increase of E g in presence of magnetic field for Bi 0.90 Sb 0.10 and Bi 0.86 Sb 0.14 is due to the lifting of degeneracy of energy levels. 32 high as 325% has been obtained for Bi 0.86 Sb 0.14 at 15 T magnetic field without any sign of saturation.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…32 The Bi rich semiconducting Bi 1Àx Sb x alloys discussed here possess similar band picture. 27,30 Hence, in accordance with Baraff, it is justified to assume that observed increase of E g in presence of magnetic field for Bi 0.90 Sb 0.10 and Bi 0.86 Sb 0.14 is due to the lifting of degeneracy of energy levels. 32 high as 325% has been obtained for Bi 0.86 Sb 0.14 at 15 T magnetic field without any sign of saturation.…”
mentioning
confidence: 73%
“…27,28 In the present work, we report temperature and magnetic field dependent resistivity of a direct band gap (Bi 0.90 Sb 0.10 ) and an indirect band gap (Bi 0.86 Sb 0.14 ) Bi-Sb alloy. Giant non-saturating MR at low temperature has been reported in polycrystalline Bi 1Àx Sb x (x ¼ 0.10 and 0.14) samples.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Further, it is observed that, Eg decreases with increasing temperature. It is noteworthy to mention that for pristine Bi0.88Sb0.12 alloy, Eg arises due to the gap between La and Ls bands [1,6,11]. However, impurity levels due to Sb have been postulated to exist between the La and Ls bands [18].…”
Section: Resultsmentioning
confidence: 99%
“…22) band gap at x = 0.12. These are narrow Eg semiconductors with maximum Eg of about 20 meV [3,11]. However, it should be pointed out that several groups have reported maximum Eg around x=0.15 [12,13,14].…”
Section: Introductionmentioning
confidence: 99%